Envelhecimento: campo novo de estudo na psicologia - Moreira, Berenice Fialho (1982)
Old people are a new population group. Also new is the knowledge of their characteristics and of the process of aging old. Academic research on all aspects of old age has developed significantly and each year more and more studies are being made. This is almost absent in Brazil. At the same time, old people are becoming increasingly important from the point of view of social policy, and the whole question of social insurance and pension provision revolves primarily around the problem of how society should provide for old age. Our study is about the kind of provision for old age that is predominant in Brazil. This is the institution retirement form, the asylum. We studied three of them describing its characteristics and its internal dynamics, showing the condition of dependency of the old people living there. The specific purpose of the field study was to provide a perspective on research in the Psychology of Aging and a discussion on the preventive and profilactic role that the psychologist can have on the field of aging.